Technical modification of indirect immunofluorescent antibody test using filter paper blood eluates - De Franco, Marcello F.; Chamma, L. G. (Karger Publishers, 1973)
An indirect immunofluorescence test using small discs (0.4 cm in diameter) cut from blood smears on filter paper is described. Discs plus three drops of phosphate-buffered saline are laid on antigenic areas on slides, which are then incubated. During incubation, eluted antibodies react with antigen. The method was tested with 10 eluates from healthy persons and with 30 eluates from three groups of 10 patients with Chagas’ disease, schistosomiasis Mansoni and South American blastomycosis, respectively. Sera from the same blood samples were tested also by conventional indirect immunofluorescence tests. Both tests gave similar results. The method proposed is useful as a rapid qualitative screening test when dealing with a large number of samples. © 1973 S. Karger AG, Basel.